Modeling and Simulation of a modern renewable energy to be used in a urban and far Iraqi areas (Journal of the College of Basic Education, 2022)
This research aims to model and simulate the transient and steady state behavior of wind turbine systems. This work could have a broad scope, that being the ease, in aims to lay groundwork which will allow for further investigation and for the development of a more sophisticated micro-turbine model. More specifically it involves modeling a micro turbine and a wind turbine block sets, and time allowing combining these models to form a micro-grid